Evaluating the Effectiveness of Floating and Suspended Materials for Reducing Evaporation Losses in Small Water Bodies - Yadima, S. G.; Ibiang, I. O.; Jones, A. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Evaporation is recognized as environmental process which can significantly reduce the quality and quantity of stored water available for industrial, agricultural and household purposes. However, this process is dependent on several meteorological factors such as water and air temperature, wind speed and atmospheric humidity. Thus, water savings especially in regions experiencing little rainfall resulting in low runoff events is crucial to enhanced optimum water usage by adopting the use of cover materials on ponds. Covering of water bodies could effectively help in reducing evaporation from open water bodies. This research aimed at investigating the effectiveness of two locally available materials, viz; plastic paint covers and weaved thatch grass. They are used as floating and suspended covers respectively for reducing evaporation. Three evaporation pans were used in this study. One pan was left uncovered as control (Pan C), another pan was covered with plastic paint covers (Pan A) while the last pan was shaded with weaved thatch grass (Pan B). Data were collected during dry season on weekly basis at 6:00 pm. This time-window was chosen because it is the hottest and driest months in Maiduguri. Sensitivity analysis was conducted between evaporation and climatic variables. The results show that evaporation is strongly correlated with temperature with R2 values of 0.8930, 0.9438 and 0.9566 for pans A, B and C respectively. It was also observed that the maximum monthly average percentage reduction (water savings) was found for Pan A to be 39.43%, 42.38%, 33.27%, and 45.14% compared to Pan B with 17.98%, 20.10%, 9.21%, and 32.55% for the months of March, April, May and June respectively. This comparison was relative to Pan C as baseline data. Additionally, plastic paint cover was found to be a good material for reducing evaporation from open water body compared to the suspended weaved thatch. Therefore, Plastic paint cover is recommended for use in reducing evaporation losses in small water bodies.